Assessment of Physico-Chemical Analysis of Ground Water Quality in Rural Area: Kampung Chendrawasih, Pekan Pahang for Drinking Purpose - Abdul Syukor, Abd Razak; Nur Azzimah, Zamri; Norbaizurah, Rahman; Suryati, Sulaiman; Munirah, T. K.; Shazarina, M. N.; Zularisam, A. W.; Edriyana, Abd Aziz; Suriayanti, N. M. Z. (Knowledge Transfer Centre, USM, 2016)
Ground water is the main sources for Kampung Chendrawasih, Pekan, Pahang as drinking water as well as for agricultural purposes such as bananas, pineapples and paddy. Nevertheless, the water quality of ground water has been degraded due to existing of heavy metal, high turbidity, biological oxygen demand (BOD), chemical oxygen demand (COD) and color. Declining water quality has been global issues of concern as it has the greatest impact on public health which lead to various types of diseases such as headaches, nausea and loss of appetite. In this research, the suitability of ground water quality of well located in Kampung Chendrawasih, in district of Pahang state was assessed for drinking purpose based on the various water quality parameters. Standard methods and techniques of water quality determination for ground water samples were employed. Based on the assessment result of ground water samples in Kampung Chendrawasih from various parameters indicates that ground water is chemically unsuitable for drinking purpose. Thus, the ground water from this place needs to be treated and cannot be directly use as drinking water supply. Furthermore, there are still no existing piping system from Pengurusan Air Pahang (PAIP) provided at this village. Based on the questionnaire conducted by Universiti Malaysia Pahang to the villages, it demonstrates that high demand for clean water from the village residents to purify the existing ground water supply. From the water quality results, it shows that the quality of Kampung Chendrawasih ground water can be enhanced by using WASRA treatment system.